Design of depth-control planting unit with single-side gauge wheel for no-till maize precision planter - Rui, Zhang; Tao, Cui; Dandan, Han; Dongxing, Zhang; Kehong, Li; Yunxia, Wang; Xiaowei, Yin; Xiantao, He; Li, Yang (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: No-till planters are very popular for maize seeding in fields covered with residue in annual wheat-maize double cropping system in North China Plain. However, there is no suitable depth control mechanism for existing no-till maize planters, and as a result, it is hard to obtain consistent planting depth, uniform emergence, and good passing ability at the same time. For the above reasons, a proper planting unit with a new type of depth-control mechanism was developed in this study. The mechanism consists of a single-side gauge wheel, a parallel four-bar linkage, a pair of double-disc opener, a V-shape press wheel and a depth regulator, which can adjust the planting depth from 30 mm to 90 mm to satisfy the agronomic requirement under different field conditions. Based on analysis and calculation, the width of gauge wheel was set to 50 mm while the length of parallel four-bar linkage was set to 350 mm. Field experiment was conducted and the results indicated that the newly designed planting unit with single-side gauge wheel performed well with regard to planting depth uniformity and anti-blocking ability. The planting depth uniformity and seed spacing quality were 95.45% and 91.90%, respectively, when the average height of stubble was 22.5 cm and residue amount was 0.64 kg/m2 in the field. It can satisfy the requirement of no-till maize planting on the cropland with residue and stubble in North China Plain.Keywords: no-till planter, maize precision planter, planting unit, depth control, single-side gauge wheel, residue, stubbleDOI: 10.3965/j.ijabe.20160906.2394Citation: Zhang R, Cui T, Yin X W, Zhang D X, Li K H, Han D D, et al. Design of depth-control planting unit with single-side gauge wheel for no-till maize precision planter. Int J Agric & Biol Eng, 2016; 9(6): 56－64.